Peningkatan Hasil Belajar pada Pembelajaran Tematik Terpadu dengan Model Kooperatif Numbered Heads Together (NHT) - Sari, Devita; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
This study aims to determine the improvement of student learning outcomes in integrated thematic learning with the cooperative model Numbered Heads Together (NHT) in class V SD Negeri 16 Kampung Nan VI, Lubuk Sikaping District. This type of research is classroom action research using qualitative and quantitative approaches. This study was a teacher (practitioner) and 20 students. The results showed an increase in a). RPP cycle I averaged 82.15% with Good qualifications (B) increased in cycle II 92.85% with Very Good qualifications (SB), b) Implementation in the teacher aspect of cycle I averaged 82.81% with qualifications Good (B) increased in Cycle II 93.75% with very good qualifications (SB). While the implementation of the aspects of students in cycle I averaged 81.25% with good qualifications (B) increased in Cycle II 93.75% with very qualifications  good (SB), c). Assessment of student learning outcomes in cycle I an average of 72.92 with sufficient qualifications (C) increased in cycle II 82.80 with good qualifications (B).